The Role of Regulatory B cells in Kidney Diseases - Long, Wang; Zhang, Hedong; Yuan, Wenjia; Lan, Gongbin; Lin, Zhi; Peng, Longkai; Dai, Helong (Frontiers in Immunology, 2021)
B cells, commonly regarded as proinflammatory antibody-producing cells, are detrimental to individuals with autoimmune diseases. However, in recent years, several studies have shown that regulatory B (Breg) cells, an immunosuppressive subset of B cells, may exert protective effects against autoimmune diseases by secretion of inhibitory cytokines such as IL-10. In practice, Breg cells are identified by their production of immune-regulatory cytokines, such as IL-10, TGF-β, and IL-35, however, no specific marker or Breg cell-specific transcription factor has been identified. Multiple phenotypes of Breg cells have been found, whose functions vary according to their phenotype. This review summarizes the discovery, phenotypes, development, and function of Breg cells and highlights their potential therapeutic value in kidney diseases.